2017
DOI: 10.1590/s0102-865020170080000005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperin protects against cisplatin-induced liver injury in mice

Abstract: Purpose: To evaluate the effect of hyperin in cisplatin-induced liver injury in mice. Methods: Mice were pretreated with hyperin at doses of 25 mg/kg and 50 mg/kg, respectively, for six days, and intraperitoneal injection of cisplatin (40 mg/kg) was administrated one hour after the final intragastrication of hyperin. Twenty-four hours later, blood and liver were collected for further research. Results: A single injection of cisplatin (40 mg/kg) for 24 h significantly increased serum alanine and aspartate amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
5
18
0
Order By: Relevance
“…Whilst, both groups II and III showed; a highly significant increase P<0.01 in the concentrations of BUN, creatinine, and urea, respectively. The current findings were similar to those of (51,52). The biochemical changes in the current study may be due to that the drug causes a reduction in the glutathione concentration (which plays an important role in removing many toxic metabolites) in the tissue of the maternal liver, kidneys, and that seems to have the main role in disturbing the cellular antioxidant regulation.…”
Section: Discussionsupporting
confidence: 85%
“…Whilst, both groups II and III showed; a highly significant increase P<0.01 in the concentrations of BUN, creatinine, and urea, respectively. The current findings were similar to those of (51,52). The biochemical changes in the current study may be due to that the drug causes a reduction in the glutathione concentration (which plays an important role in removing many toxic metabolites) in the tissue of the maternal liver, kidneys, and that seems to have the main role in disturbing the cellular antioxidant regulation.…”
Section: Discussionsupporting
confidence: 85%
“…GSH-Px is an important enzyme that catalyzes the decomposition of hydrogen peroxide, which in turn, protects cell membranes and prevents cell damage [ 32 ]. MDA is a metabolite of lipid peroxidation; a high content of MDA accumulates in the body after liver injury [ 33 ]. In this study, we found that PLT could significantly regulate the levels of SOD, GSH-Px, and MDA in the body caused by liver injury, thereby protecting the liver from the effects of carbon tetrachloride.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cell, the hydrolysis of CP generates positively charged toxic platinum ions, which preferentially accumulate within the negatively charged mitochondria and lead to the overproduction of reactive oxygen species (ROS). [ 9,10 ] This consequently suppresses oxidative phosphorylation, as well as the activities of antioxidant enzymes, thus contributing to mitochondrial dysfunction. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%